African Disability Rights Yearbook Volume 4 2016 - Charles Ngwena (Pretoria University Law Press (PULP), 2016)
About the publication The African Disability Rights Yearbook addresses disability rights within the foundational structure laid down by the inaugural issue. The structure comprises a tripartite division between: articles; country reports; and shorter commentaries on recent regional and sub-regional developments. The African Disability Rights Yearbook aims to advance disability scholarship. Coming in the wake of the United Nations Convention on the Rights of Persons with Disabilities, it is the first peer-reviewed journal to focus exclusively on disability as human rights on the African continent. It provides an annual forum for scholarly analysis on issues pertaining to the human rights of persons with disabilities. It is also a source for country-based reports as well as commentaries on recent developments in the field of disability rights in the African region. The African Disability Rights Yearbook publishes peer-reviewed contributions dealing with the rights of persons with disabilities and related topics, with specific relevance to Africa, Africans and scholars of Africa. The Yearbook appears annually under the aegis of the Centre for Human Rights, Faculty of Law, University of Pretoria. The Yearbook is an open access online publication, see www.adry.up.ac.za About the editors: Charles Ngwena is Professor, Department of Constitutional Law and Legal Philosophy, Faculty of Law, University of the Free State, South Africa. Ilze Grobbelaar‐du Plessis is a senior lecturer and holds the degrees BIuris LLB LLM LLD from the University of Pretoria. Helene Combrinck is Associate Professor at the Centre for Disability Law and Policy, University of the Western Cape. Serges Djoyou Kamgais is Senior Lecturer at TMALI (UNISA). Table of Contents Stigma as barrier to the implementation of the Convention on the Rights of Persons with Disabilities in Africa Mark Mostert Realising the inclusion of youth with disabilities in political and public life in Kenya Lucianna Thuo Reading 'disability' into the non-discrimination clause of the Nigerian Constitution Ngozi Chuma Umeh Legislative mechanisms for combating violence against children with disabilities in selected African jurisdictions: A critical appraisal Enoch Chilemba My right to know: Developing sexuality education resources for learners with intellectual disability in the Western Cape, South Africa Rebecca Johns Colleen Adnams (Re)thinking sexual access for adolescents with disabilities in South Africa: Balancing rights and protection Paul Chappell The development and use of Sign Language in South African schools: The denial of inclusive education Willene Holness Implementing article 33 of CRPD: Tanzanian approach Abdallah Possi SECTION B: COUNTRY REPORTS Angola Eduardo Kapapelo Gabon Christophe Tchudjo Victorine Maptue Toguem Senegal Abdoulaye Thiam Seydi Ababacar Sy Sow SECTION C: REGIONAL DEVELOPMENTS The jurisprudence of the committee on the rights of persons with disabilities and its implications for Africa Innocentia Mgijima The right to work and employment in Southern Africa: A commentary on how selected employment laws fare against article 27 of the CRPD Dianah Msipa BOOK REVIEW Don Kulick & Jens Rydström Loneliness and its opposite: Sex, disability, and the ethics of engagement (2015) Paul Chappell